Bullying Victimization and Life Satisfaction Among Rural Left-Behind Children in China: A Cross-Sectional Study - Yang, Yide; Zheng, Chanjuan; Xie, Ming; Yuan, Shuqian; Zeng, Yuan; Zhou, Meiling; Huang, Shuzhen; Zhu, Yulian; Ye, Xiangli; Zou, Zhiyong; Wang, Ying; Baker, Julien Steven (Frontiers in Pediatrics, 2021)
Objectives: This study aimed to evaluate the associations between bullying victimization and life satisfaction in primary school children, and also investigate the interactive effects of left-behind status and bullying victimization on life satisfaction. Materials and methods: Bullying victimization was measured using the Chinese version of the revised Olweus Bully/Victim Questionnaire. Life satisfaction was assessed using the Multidimensional students’ life satisfaction scale (MSLSS). Life satisfaction is composed of 5 domains, including family, school, friends, environment, and self-satisfaction. Left behind status of rural children was defined as one or both their parents migrating to working in cities. The data was analyzed using Mann-Whitney U tests, Chi-square tests, multivariate linear and logistic regression analyses. Results: A total of 810 primary school children were involved, of which 8.5% reported bullying victimization, 44.3% were left behind children (LBC). We found that bullying victimization was negatively associated with all domains of life satisfaction (all P<0.05). With further left behind status-stratified analysis, we found that negative association between bullying victimization and friend satisfaction was more profound in the LBC group than the non-LBC group [b(SE)= -0.133(0.03) vs -0.061(0.026) for LBC and non-LBC, respectively, P<0.05]. When further interaction analysis was conducted, we identified interaction effects between left behind status and bullying victimization on friend satisfaction (Pinteraction=0.048). Similar interaction effect between bullying victimization and left behind status on school satisfaction was also found (Pinteraction=0.004). Conclusions: Bullying victimization was associated with low life satisfaction (including lower family, friends, school, self and environment satisfaction). There were significant interactions between left-behind status and bullying victimization on friend satisfaction, as well as school satisfaction. Left behind status of children may exaggerate the impact of bullying victimization on friends/school satisfaction rating.